Carbon Emissions: A Bibliometric Analysis Using Biblioshiny - Ani Pujiati; Yuliansyah Yuliansyah; Chara Pratami Tidespania Tubarad; Sudrajat Sudrajat (Review of Multidisciplinary Academic and Practice Studies, 2026)
Purpose: This study aims to analyze the development of research related to Environmental Management Accounting (EMA) and carbon emissions using a bibliometric approach. The main objective is to identify research trends, intellectual structure, and future research directions in this field. Methodology: The study employs a bibliometric analysis using Biblioshiny software. Data were retrieved from the Scopus database, consisting of 200 documents published between 2015 and 2025. The analysis includes publication trends, most productive authors, countries, institutions, journals, keyword co-occurrence, thematic mapping, and trendtopic analysis. Results: The findings indicate a significant increase inpublications related to EMA and carbon emissions, particularly after 2020, driven by growing global concerns about sustainability, climate change, and green accounting practices. Conclusion: The study concludes that research on EMA and carbon emissions is rapidly expanding and becoming more interdisciplinary, with increasing focus on sustainability-driven accounting practices. Limitations: This study is limited to Scopus-indexedpublications and may not capture relevant studies from other databases or grey literature sources. Contributions: This study contributes by providing acomprehensive overview of the intellectual structure of EMA and carbon emission research and offers insights into future research directions in sustainability accounting.